Why do SMEs not borrow more from banks? Evidence from the People's Republic of China and Southeast Asia - Ganeshan Wignaraja; Yothin Jinjarak (Asian Development Bank Institute (ADBI), 2015)
This study examines the relationship between firm characteristics and borrowing from commercial banks by small and medium-sized enterprises (SMEs) in the People's Republic of China (PRC) and five Southeast Asian economies (Indonesia, Malaysia, the Philippines, Thailand, and Viet Nam). Analysis of microdata from enterprise surveys highlights key aspects of SME finance since the global financial crisis, including sources of credit, lender types, and collateral types. First, SMEs typically resort to internal sources rather than external finance (including borrowing from banks) and trade credit. Second, when it comes to external finance, SMEs typically use informal non-bank credit sources more than banks. Third, there is a positive and significant association between bank borrowing and certain characteristics of SMEs, notably financial audits, firm age, and export participation. Fourth, personal assets of SME owners tend to matter more as collateral for SME borrowing from banks than other collateral types. Improving credit guarantee systems, enhancing monitoring and credit scoring by banks, and widening the scope of collateral are possible ways to facilitate increased bank borrowing by SMEs.
Keywords: D22; E44; F14; L16; O14; 330; credit access; firm-level survey; collateral; credit guarantees; smes